Surface-tuned Co3O4 nanoparticles dispersed on nitrogen-doped graphene as an efficient cathode electrocatalyst for mechanical rechargeable zinc-air battery application - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
The most vital component of the fuel cells and metal air batteries is the electrocatalyst, which can facilitate the oxygen reduction reaction (ORR) at a significantly reduced overpotential. The present work deals with the development of surface-tuned cobalt oxide (Co3O4) nanoparticles dispersed on nitrogen-doped graphene as a potential ORR electrocatalyst possessing some unique advantages. The thermally reduced nitrogen-doped graphene (NGr) was decorated with three different morphologies of Co3O4 nanoparticles, viz., cubic, blunt edged cubic, and spherical, by using a simple hydrothermal method. We found that the spherical Co3O4 nanoparticle supported NGr catalyst (Co3O4-SP/NGr-24h) has acquired a significant activity makeover to display the ORR activity closely matching with the state-of-the-art Pt supported carbon (PtC) catalyst in alkaline medium. Subsequently, the Co3O4-SP/NGr-24h catalyst has been utilized as the air electrode in a Zn-air battery, which was found to show comparable performance to the system derived from PtC. Co3O4-SP/NGr-24h catalyst has shown several hours of flat discharge profile at the discharge rates of 10, 20, and 50 mA/cm(2) with a specific capacity and energy density of similar to 590 mAh/g(-zn) and,840 Wh/kg(-zn), respectively, in the primary Zn-air battery system. In conjunction, Co3O4-SP/NGr-24h has outperformed as an air electrode in mechanical rechargeable Zn-air battery as well, which has shown consistent flat discharge profile with minimal voltage loss at a discharge rate of 50 mA/cm(2). The present results, thus demonstrate that the proper combination of the tuned morphology of Co3O4 with NGr will be a promising and inexpensive material for efficient and ecofriendly cathodes for Zn-air batteries.
Keywords: electrocatalyst; mixed facets; oxygen reduction reaction; rechargeable zinc-air battery; surface morphology